STEPHEN H. KENDALL, JOHN R. DALE (ed.) - The Short Works of John Habraken / STEPHEN H. KENDALL (ed.) - Residential Architecture as Infrastructure. Open building in Practice / STEPHEN H. KENDALL, N. JOHN HABRAKEN (ed.) - Open Building for Architects. Professional Knowledge for an Architecture of Everyday Environment - Montaner, Josep M. (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
STEPHEN H. KENDALL, JOHN R. DALE (eds.)The Short Works of John HabrakenRoutledge, Taylor & Francis Group, Londres y Nueva York, 2023, 516 pp. Tapa dura, 61,59 £ Idioma: inglésISBN: 978-0-367-82007-7STEPHEN H. KENDALL (ed.)Residential Architecture as Infrastructure. Open building in PracticeRoutledge, Taylor & Francis Group, Londres y Nueva York, 2022, 408 pp. Tapa blanda, 26,39 £Idioma: inglésISBN: 978-0-367-86313-5STEPHEN H. KENDALL, N. JOHN HABRAKEN (eds.)Open Building for Architects. Professional Knowledge for an Architecture of Everyday EnvironmentRoutledge, Taylor & Francis Group, Londres y Nueva York, 2024, 234 pp. Tapa blanda, 26,39 £Idioma: inglésISBN: 978-1-032-15214-1